Dog man : For whom the ball rolls - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2019)
"The Supa Buddies have been working hard to help Dog Man overcome his bad habits. But when his obsessions turn to fears, Dog Man finds himself the target of an all-new supervillain! Meanwhile, Petey the Cat has been released from jail and starts a new life with Li'l Petey. But when Petey's own father arrives, Petey must face his past to understand the difference between being good and doing good."--Publisher.
"Treehouse Comix proudly presents."
English
Keywords: Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Dogs -- Comic books, strips, etc; Dogs -- Juvenile fiction; Good and evil -- Comic books, strips, etc; Heroes -- Comic books, strips, etc; Police -- Comic books, strips, etc; Police -- Juvenile fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Cats -- Fiction; Dogs -- Fiction; Graphic novels; Humorous stories; Police -- Fiction; Cats; Dogs; Good and evil; Heroes; JUVENILE FICTION / Comics & Graphic Novels / Action & Adventure; JUVENILE FICTION / Comics & Graphic Novels / Humorous; JUVENILE FICTION / Comics & Graphic Novels / Superheroes; Police; Action and adventure comics; Humorous comics; Graphic novels; Action and adventure comics; Action and adventure comics; Comic books, strips, etc; Fiction; Graphic novels; Graphic novels; Humorous comics; Humorous comics; Juvenile works